2011
DOI: 10.1002/jps.22727
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical stability of solid dispersions of enantiomeric or racemic ibuprofen in stearic acid

Abstract: ABSTRACT:The aim of this study was to investigate the solid dispersion phase behavior of S-or RS-ibuprofen in stearic acid. By means of thermal analysis, we have demonstrated the total immiscibility, in solid state, of the corresponding binary mixtures. This indicates that no specific interactions exist between the chosen excipient and active pharmaceutical ingredient (API) that lead to eutectic systems. Furthermore, based on calorimetric and X-ray diffraction experiments, we have showed that upon cooling of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 27 publications
4
8
0
Order By: Relevance
“…These findings were in agreement with Kobayashi (1988), who stated that only the thermostable C-form could be formed from a melt [31]. In contrast, Corvis et al (2011) reported recrystallization of stearic acid in the Eform from a ibuprofen/stearic acid melt. However, upon heating, this polymorph converted to the thermostable C-form at about 45 °C [32].…”
Section: In Vitro Drug Releasesupporting
confidence: 91%
See 2 more Smart Citations
“…These findings were in agreement with Kobayashi (1988), who stated that only the thermostable C-form could be formed from a melt [31]. In contrast, Corvis et al (2011) reported recrystallization of stearic acid in the Eform from a ibuprofen/stearic acid melt. However, upon heating, this polymorph converted to the thermostable C-form at about 45 °C [32].…”
Section: In Vitro Drug Releasesupporting
confidence: 91%
“…However, as no solid-solid transformations were detected prior to the melting endotherms of stearic and behenic acid (i.e. 68 and 75 °C, corresponding to the melting point of the C polymorph), it indicates that only the polymorph C was present in the formulations [32]. These findings were in agreement with Kobayashi (1988), who stated that only the thermostable C-form could be formed from a melt [31].…”
Section: In Vitro Drug Releasesupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, although the said melting point of IBU is approximately 76 °C, formulations containing IBU and terfenadine are reported to melt at temperatures ranging from 50 to 76 °C [ 18 ]. This melting point depression is attributed to the tendency of IBU to form eutectic compositions, as has also been found for IBU mixtures with diphenhydramine hydrochloride, astemizole and stearic acid [ 19 ]. These compositions exhibit structural deteriorations such as crumbling, pitting and fissuring, as well as decolorization pertaining to the rise of instability and storage issues [ 18 ].…”
Section: Introductionmentioning
confidence: 54%
“…from the baseline starting before the onset of the invariant peak to the baseline after the endset of the liquidus transformation. All the Q values presented in this work were calculated from published DSC profiles [7,11,[27][28][29].…”
Section: Methodsmentioning
confidence: 99%